Cucumis Sativus L. Foamy Extract Induces Apoptosis In Mda-Mb-231 Cells: Cucumber Extract Induces Apoptosis in Cancer Cells - Kumaraswamy, Latha K; Tallur, Preethi N (SAARC Journal of Agriculture, 2025)
Cucumis sativus L. (C. sativus) is considered as an important salad fruit as well as vegetable, fruits. It is consumed as herbal medicines. Here, we investigated the effects of foamy extract on the viability of the MDA-MB-231 human cells. Results revealed that extract significantly (P < 0:05) inhibited the proliferation of cells in comparatively lower toxic effects. The IC50 was found to be 116.11 µg/mL against MDA-MB-231 cells, Annexin V/PI staining assays indicated that it stimulated apoptosis in MDA-MB-231. Treated cells were observed to show greater incidence of apoptotic cells, when compared to the untreated cells. Thus, it is efficient enough to induce apoptosis, in MDA-MB-231 cells. Cucumber foamy extract may prove to be an important source of natural anticancer agents. SAARC J. Agric., 22(2): 55-66 (2024)